Diagnóstico ambiental urbano da cidade de Novo Airão - Amazonas - Moura, Sarita de (2009)
Most of Brazil s municipalities are suffering environmental impacts. This situation is worse when we talk about small towns, where the framework for environmental policies is still precarious. In this ambit, when it comes to the urban planning of cities in the Brazilian Amazon, the situation is different, because the cities in the country s northern region usually grow along rivers, which complicates territorial development and therefore urban environmental planning. The objective of this research is to draw up an urban environmental diagnosis for the city of Novo Airão (AM) to support its land-use policies for urban expansion. This work addressed issues involving urban infrastructure and environmental sanitation, the quality of water supplied to the population, solid waste, rainwater runoff, areas vulnerable to natural risks, areas at risk of contamination (cemeteries, port, gas station), etc. Similarly to the situation of numerous other Brazilian cities, Novo Airão presented several irregularities, such as lack of sanitation in most of the city, contamination of several groundwater wells that supply the population, location of homes in areas of permanent preservation, and lack of paved streets in much of the city, among other problems.